Compressive Resistance of Abutments with Different Diameters and Transmucosal Heights in Morse-Taper Implants - Lillo,Ricardo (2015)
The aim of this study was to evaluate the compressive resistance under oblique loads of abutments with two different diameters and transmucosal heights used for cement-retained implant-supported prostheses in Morse-taper implants. Forty Morse-taper implants were divided into four groups with different abutment sizes for cement-retained prostheses in order to perform the compressive test. The groups were divided by abutment diameter and transmucosal height as follows: Group 1: 4.5 x 2.5 mm; Group 2: 4.5 x 3.5 mm; Group 3: 3.3 x 2.5 mm; and Group 4: 3.3 x 3.5 mm. An oblique compressive loading test was performed on each sample located in a platform at 30° using a universal testing machine with a load cell of 1,000 kgf and 0.5 mm/min speed until achieving the deformation of abutment's neck. The compressive resistance and its mechanical behavior were recorded for each group and the data were analyzed using ANOVA, the Shapiro-Wilk and Scheffé tests. In addition, the detailed damage of all samples was recorded with a conventional camera linked to the endoscopic equipment. Significant differences were observed among the groups, except between Groups 2 and 3 (p>0.005). All the abutments showed permanent deformations in the upper region and at the transmucosal portion, but the threads of the screws were intact. Fractures were only identified in Groups 3 and 4. Stronger mechanical behavior and compressive resistance was observed in the abutments with 4.5 mm diameter and 2.5 mm transmucosal height.